International Image Processing, Applications and Systems Conference 2014
DOI: 10.1109/ipas.2014.7043293
|View full text |Cite
|
Sign up to set email alerts
|

Object recognition for blind people based on features extraction

Abstract: Since the 1970, object recognition technologies have matured to a point at which exciting applications are becoming possible for visual substitution. In fact, industry has created a variety of computer vision products and services by developing new electronic aids for the blind in order to overcome the difficulties that the dog and cane do not respond. This paper provides an overview of various visual substitution systems developed in the recent years. It aims also to introduce a proposed method that restores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The ORB algorithm's speed is the fastest of the SIFT and SURF algorithms based on the experimental results. In a previous study [5], the accuracy and speed in processing a video frame in the SIFT and SURF algorithms are inversely related. In this study, besides the ORB algorithm is the fastest in processing a frame, the L 5 value of the ORB algorithm is 0.81, which is not much different from the SIFT algorithm of 0.97 and better than the SURF algorithm, which is only 0.73.…”
Section: E Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The ORB algorithm's speed is the fastest of the SIFT and SURF algorithms based on the experimental results. In a previous study [5], the accuracy and speed in processing a video frame in the SIFT and SURF algorithms are inversely related. In this study, besides the ORB algorithm is the fastest in processing a frame, the L 5 value of the ORB algorithm is 0.81, which is not much different from the SIFT algorithm of 0.97 and better than the SURF algorithm, which is only 0.73.…”
Section: E Discussionmentioning
confidence: 94%
“…The primary stages in video processing are pre-processing by extracting video into frames and extracting features from the frame. Research conducted by Jabnoun et al [5] processed all video frames to detect household appliance objects. Processing all frames make delay in real-time video processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Panchal et al presented, in [30], a new approach for recognizing text from scene images and to convert it into speech so that it can assist VI people. Jabnoun and colleagues reported in [31] an object recognition system based on SIFT (Scale Invariant Features Transform) and SURF algorithms to assist VI people during navigation. Ciobanu et al introduced, in [32], a method for detecting indoor staircases by employing IMU (inertial measurement unit) sensors and processing depth images in order to aid VI people in unfamiliar environments.…”
Section: State Of the Art On Innovative Assistive Technology Devices mentioning
confidence: 99%
“…al. [5] in their paper said that object recognition for the visually impaired based on features extraction provided an overview of various visual alternative systems developed in the recent years. This method is based on interpretation, video analysis and feature extraction .They give the results of comparison of SIFT and SURF in which they concluded that SURF is faster than SIFT ,however SIFT is robust when the matches findings, scale variations are considered.…”
Section: Survey Detailsmentioning
confidence: 99%